Transmembrane redox control and proteolysis of PdeC, a novel type of c‐di‐GMP phosphodiesterase. (7th March 2018) - Herbst, Susanne; Lorkowski, Martin; Sarenko, Olga; Nguyen, Thi Kim Loan; Jaenicke, Tina; Hengge, Regine
Abstract: The nucleotide second messenger c‐di‐GMP nearly ubiquitously promotes bacterial biofilm formation, with enzymes that synthesize and degrade c‐di‐GMP being controlled by diverse N‐terminal sensor domains. Here, we describe a novel class of widely occurring c‐di‐GMP phosphodiesterases (PDE) that feature a periplasmic "CSS domain" with two highly conserved cysteines that is flanked by two transmembrane regions (TM1 and TM2) and followed by a cytoplasmic EAL domain with PDE activity. Using PdeC, one of the five CSS domain PDEs of Escherichia coli K‐12, we show that DsbA/DsbB‐promoted disulfide bond formation in the CSS domain reduces PDE activity. By contrast, the free thiol form is enzymatically highly active, with the TM2 region promoting dimerization. Moreover, this form is processed by periplasmic proteases DegP and DegQ, yielding a highly active TM2 + EAL fragment that is slowly removed by further proteolysis. Similar redox control and proteolysis was also observed for a second CSS domain PDE, PdeB. At the physiological level, CSS domain PDEs modulate production and supracellular architecture of extracellular matrix polymers in the deeper layers of mature E. coli biofilms. Synopsis: The bacterial secondary messenger c‐di‐GMP controls biofilm formation and extracellular matrix component secretion. C‐di‐GMP levels are controlled by degradation via c‐di‐GMP phosphodiesterases. The activity of CSS domain‐containing c‐di‐GMP phosphodiesterases PdeC and PdeB is regulated by complex posttranslational modifications in the periplasmic space. The DsbA/DsbB complex induces disulfide bond formation between conserved cysteines in the periplasmic CSS domain of PdeC. Disulfide bond formation inhibits PdeC activity and proteolytic cleavage by periplasmic proteases DegP/DegQ. The free thiol form of PdeC shows activity which is associated with dimerisation and cleavage in the CSS domain. A similar interplay between redox control and proteolysis was observed for the related phosphodiesterase PdeB. Active CSS domain phosphodiesterases reduce extracellular matrix biosynthesis in the deeper zones of Escherichia coli macrocolony biofilms. Abstract : A new class of c‐di‐GMP phosphodiesterases in Escherichia coli are regulated by posttranslational modifications in the periplasm to reduce biofilm formation.